Previsão de propriedades de transporte: viscosidade em biolubrificantes e tensão interfacial de misturas de hidrocarbonetos-CO2-H2O - Frutuoso, Luis Felipe Alves (2024)
Current global research trends in environmental sustainability has urged the development of new products and technology. The synthesis of vegetable oil-based biolubricants and the carbon capture and storage technologies (CCS) have attracted particular attention in this issue. This work carried out molecular dynamics calculations in order to evaluate the transport and thermodynamic properties of some fluids in different conditions. The viscosity of biolubricants and the interfacial tension of mixtures of hydrocarbons, water and carbon dioxide (CO2) mixtures were the properties considered. The viscosity of seven different structure biolubricants (BL1, BL2, BL3, C30-BPAOL1, 18-2-18, 18-9-18 e T-TMPE) was evaluated in the NPT ensemble with the CVFF force field employing non-equilibrium molecular dynamics (NEMD) and equilibrium molecular dynamics (EMD). To our knowledge, this is the first theoretical study combining two different techniques with a general force field to evaluate the viscosity of distinct products. The results showed a good agreement with experimental data from the literature, exhibiting sensitivity to variations in molecular structure, pressure and temperature. We observed that increasing temperature or pressure would cause a decrease in viscosity for all the molecules considered. The interfacial tension was calculated by using a coarse-grained model with the SAFT- Mie force field with the aid of the temperature-quench molecular dynamics (TQMD) technique. The methodology was validated for the methane, water and CO2 mixture. We studied the interfacial tension of the mixture of propane, water and CO2 at the temperatures of 298, 333 and 373 K, ranging the pressure from 5 to 20 MPa at CO2 concentration up to 80%. The results showed that the interfacial tension decreases with increasing temperature, pressure and CO2 concentration. Additionally, we have tested the influence of the hydrocarbon chain by using a mixture of n-decane, water and CO2. Our results showed an increase in interfacial tension with a longer hydrocarbon chain. The analysis of the atomic density profiles provide evidence of the local enrichment of carbon dioxide at the interface in the studied systems, yielding a correspondence of the observed effects.